2013
DOI: 10.3855/jidc.2290
|View full text |Cite
|
Sign up to set email alerts
|

Insight and educational intervention concerning hepatitis among roadside barbers and their clients in Karachi, Pakistan

Abstract: Introduction: This study aimed to determine perceptions of hepatitis and make available an educational intervention session regarding the infection among roadside barbers and their clients. Methodology: A cross-sectional study using convenience random sampling technique was conducted on all barbers and one each of their clients during January to June, 2011, in Karachi, Pakistan. After informed consent was taken and confidentiality ensured, respondents answered an anonymous questionnaire of closed-ended questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 11 publications
3
11
0
Order By: Relevance
“…The results of this study revealed that none of them were practicing instrument decontamination and sterilization. Similar views have been reported in previous studies in Iran, (Almasi et al, 2016) South Africa (James et al, 2017) and Pakistan (Shahid et al, 2013). Findings reveal that barbers only clean their instruments with brush, wet cloth and oil the machines when required.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this study revealed that none of them were practicing instrument decontamination and sterilization. Similar views have been reported in previous studies in Iran, (Almasi et al, 2016) South Africa (James et al, 2017) and Pakistan (Shahid et al, 2013). Findings reveal that barbers only clean their instruments with brush, wet cloth and oil the machines when required.…”
Section: Discussionsupporting
confidence: 89%
“…In view of the above barbering operations in Fiji may expose a large proportion of its clients with several health hazards silently if preventive measures are continued to be ignored as demonstrated by previous studies. (Amir & Raymond, 2005;Shahid et al, 2013). Considering the grave consequences of infections especially Hepatitis, HIV and recent outbreak of COVID19, related to barbers' profession; bona fide barbering practices is imperative to control infections associated with this profession (Janjua & Nizamy, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…12,68,69 A number of educational interventions have been undertaken in Pakistan over the past decade to tackle community and general 36 risk exposures such as barbering, tattooing, and body piercing. [36][37][38]70 For instance, in 2014/2015, the Health Foundation 71 developed an HCV educational intervention in Karachi, Pakistan, that aimed to educate the general public on healthcare and community risk factors through health educator volunteers and electronic and print media. A similar intervention is being done in Azad Kashmir in Northern Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…32 Recently, WHO launched a new global policy on injection safety to be piloted in a number of countries. 33 In Pakistan, since 2005 a number of major hepatitis prevention and control programs 34,35 have focused on ensuring safe blood transfusions, improving disposal of syringes, increasing public awareness, and educating healthcare professionals and barbers [36][37][38] ; but unfortunately, the effectiveness of these interventions in reducing HCV transmission in Pakistan is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…While nearly 90% of them did not agree on regular public screening programs against blood-borne infectious diseases, 97% were willing to be tested for these infections. The status of these professions becomes even more problematic because barbers in some rural communities in Pakistan also provide other services, such as circumcision, incisions, and wound drainage (25, 26). …”
Section: Discussionmentioning
confidence: 99%